Specific Comparison of Dispute Resolution Mechanisms Between China and Laos - PHONPARSITH, bounthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The objectives of this research were to: (1) compare the types of dispute resolution mechanisms between China and Laos, (2) compare the structures of these mechanisms in both countries, and (3) analyze the similarities and differences in their overall dispute resolution systems. The study employs a qualitative comparative approach to identify commonalities and distinctions in litigation, mediation, and arbitration practices. The findings reveal that both China and Laos share a cultural emphasis on harmony and mediation rooted in their Asian legal traditions, yet they differ significantly in institutional development and procedural formality. China’s dispute resolution framework is diversified and highly institutionalized, integrating state-led mechanisms such as mediation, arbitration, and litigation, supported by digital innovation and ongoing legal reforms. In contrast, Laos maintains a socially driven model that relies heavily on community-based mediation grounded in Buddhist traditions and moral reconciliation. While China’s system ensures greater procedural certainty and enforceability, the Laotian approach prioritizes accessibility and social cohesion but lacks institutional standardization and international recognition. The study concludes that variations in institutional capacity, cultural values, and legal infrastructure strongly influence the effectiveness of dispute resolution in both countries. It recommends strengthening cross-border coordination, establishing joint arbitration frameworks, and developing hybrid models that integrate formal and informal mechanisms to enhance efficiency, fairness, and regional legal integration under the Belt and Road Initiative.